ANALISIS PERAN BELANJA MODAL DAN INVESTASI SWASTA TERHADAP PERTUMBUHAN EKONOMI SERTA DAMPAKNYA PADA KESEJAHTERAAN MASYARAKAT - Akhlis Priya Pambudy; Muhamad Imam Syairozi (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2019)
The purpose of economic development is to improve public welfare. Many factors influenceeconomic growth, including sustainable development. This study is aimed to analyze the impactof capital expenditure and private investment on economic growth of the regency/municipalduring the period of 2010-2015 as well as the impact of economic growth on public welfareproxied by the human development index figures. Using WarpPLS, used purposive samplingmethode, testing is done for the 415 autonomous regional and 93 autonomous municipalsin Indonesia using time series data 2010-015. The results of this study shows that capitalexpenditure positively effect economic growth as well as private investment has positive effecton economic growth. Furthermore, the economic growth has been proven to improve publicwalfare.Keywords: capital expenditure, private investment, economic growth, public welfare